Measures and optimization methods of communications network energy efficiency - Xiuying NIE (Dianxin kexue)
Although network played an important role in energy efficiency improvement for many industries,network energy consumption had threatened the sustainable development of network operators,due to the fast increasing of the networks’ energy consumption recent years as the swift development of internet users,internet services and applications.The energy consumption risk faced by network operators,the research development of the measures and optimization methods of network energy efficiency was introduced.The energy efficiency optimization in the future network was finally concluded.